Menemukan Universalitas Pesan Alquran Sebagai Keniscayaan dalam Penafsiran Multi-Interdisipliner - Wardani, Wardani; Nadhiroh, Wardatun (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2018)
This article aims to lay a philosophical foundation on the universality of the message of the Qur’an as a necessity in a multi-interdisciplinary approach to interpreting the Qur’an. The study departs from the thoughts of Qur’anic scholars from the classical to the contemporary period as set out in their works. The “universality” here means two senses: first, compatibility of the message, owing to its universal and perennial ethical contents, to be applied across boundaries of time and space; second, various aspects of contents of the Qur’an, such as theological, legal, ethical, and scientific issues. This article also suggests methods in exploring the universality of the Qur’anic doctrines and gives one example of its application, especially in understanding Quranic values in its doctrine of warfare. The authors conclude that an integrative approach to the Qur’an is needed to be accompanied by an awareness of the universality of the message of the Qur’an which lies in the spirit of ethical principles and the need for meaning in a broader spectrum in the modern era. Neglecting its universal message will cause interpretations to lose this spirit, such as classical Moslem interpreters’ understanding on jihad-verses by insisting that the jihad as warfare is a permanent obligation upon Moslems. The falsehood of the interpretation is due to neglecting the ethical principle i.e. humanity behind the law of reciprocity that underlies particular verses on warfare.